Digital Competence Transformation For MSME Adaptation Toward Consumer Behavior Disruption in Banda Aceh - Aida Fitri; Muhammad Jaka Wirata; Aidila Sukma (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background – The rapid development of digital technology and changes in consumer behavior have encouraged MSMEs to adapt quickly through strengthening digital competencies. Previous studies have generally focused on the effect of digital competence on business performance; however, limited research explains how digital competence transformation supports MSME adaptive capability in responding to consumer behavior disruption, particularly in the context of MSMEs in Banda Aceh. In addition, the mediating role of business performance in this relationship remains underexplored. Therefore, this study addresses the research gap by examining the effect of digital competence transformation on MSME adaptive capability through business performance based on the Dynamic Capabilities Theory Aim – This study aims to analyze the effect of digital competence transformation on MSME adaptive capability, with business performance serving as a mediating variable. Design / methodology / approach – This study employed a quantitative approach involving 300 MSMEs in Banda Aceh selected through simple random sampling. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Findings – The results indicate that digital competence transformation has a positive and significant effect on both business performance and MSME adaptive capability. Business performance was also found to significantly mediate the relationship between digital competence transformation and adaptive capability. Conclusion – Digital competence transformation plays an important role in improving MSME performance and strengthening adaptive capability in responding to consumer behavior disruption. These findings support the Dynamic Capabilities Theory. Research implication – This study highlights the importance of strengthening digital competencies and adaptive business strategies through training programs and policy support to enhance MSME competitiveness. Limitations – This study is limited to MSMEs in Banda Aceh and uses a quantitative approach; therefore, the findings may not be fully generalized to other contexts.